SISTEM KETIDAK SEIMBANGAN BEBAN PADA JARINGAN TEGANGAN RENDAH MENGGUNAKAN ALAT PHB – SR ( PERALATAN HUBUNG BAGI SAMBUNGAN RUMAH) DI PT. PLN PERSERO ULP BINJAI TIMUR - Siddik, Muhammad; -, Hamdani; Satria, Beni (Politeknik Harapan Bersama Tegal, 2024)
Load imbalance in an electric power distribution system often occurs in the field. This is a single-phase load on Low Voltage Network customers that is not the same due to the large number of additional electrical loads that do not pay attention to system load imbalances. As a result of this imbalance, a current appears in the transformer neutral. The current flowing in the neutral of the transformer causes losses, namely losses due to neutral current in the neutral conductor of the transformer and losses due to neutral current flowing to the ground. By realizing PHB SR (Home Connection Equipment) is able to balance the load on the Low Voltage Network. balance the load on the Low Voltage Network periodically and continuously so as to reduce technical shrinkage (losses), simplify the Connection Field in the technical connection of the Low Voltage Network. Connection in the technical connection of the House Connection (SR) on the pole, improve the aesthetics and neatness of the Network System.